Characterization and Sorption Study of Cesium-137 by Bentonite from Santrijaya, Indonesia as an Engineering Barrier Material for Radioactive Waste Disposal Facilities - Sriwahyuni, H.; Krisnandi, Y. K.; Basuki, T.; Setiawan, B.; Budianti, A.; Anggraini, Z.; Nurliati, G.; Pamungkas, N. S. (Atom Indonesia, 2025)
Engineered barrier materials, such as bentonite, play a critical role for the safety of radioactive waste disposal systems by limiting radionuclide migration. This study aims to evaluate the mineralogical, chemical, and morphological characteristics of natural bentonite from Santrijaya, Tasikmalaya, Indonesia, and to investigate its Cs-137 sorption behavior, focusing on its potential as a candidate for engineered barrier materials. X-Ray Diffraction (XRD) and X-Ray Fluorescence (XRF) analyses showed that the bentonite predominantly consists of montmorillonite, with silica contributing about 80 percent of its composition. The material shows a specific surface area of 121.89 m²/g and a cation exchange capacity of 43.23 meq/100g, supporting its suitability for radionuclide sorption. The sorption capacity at equilibrium (q_e) achieved at 536.67 mg-Cesium/g-bentonite after 10 days of contact time, with adsorption kinetics that follows the Pseudo-Second Order (PSO) model and the distribution coefficient (K_d) value of 5211 mL/g. The study shows the competitive effects of K+ and Na+ ions, with K+ ions showing a stronger competitiveness for Cs-137 binding sites than that of Na+, which could influence radionuclide retention. These findings highlight the high sorption efficiency and stability of Santrijaya bentonite, showing its potential as a barrier material for radioactive waste containment systems and suggest the necessity of considering competing ion interactions in the design of barrier materials.